Municipal Mechanized Bakery in interwar Warsaw (1928–1936): ideals and realities of a public investment - Matsuka, Jin (Studia Historiae Oeconomicae, 2025)
This study investigates the Warsaw Municipal Bakery from its inception in 1928 to its operation until 1936, a period aimed at modernizing the baking industry within interwar Warsaw. By using primary sources, including audit reports, governmental documents, and contemporary studies, this research primarily analyzes the economic strategies and public investments linked to the bakery. It examines the operational challenges – including management inefficiencies, technical obstacles, and private-sector resistance – while situating them within the broader economic policies and socioeconomic context of the time. The study further explores the gap between the intended modernization goals and the actual outcomes, highlighting the ideological and political motivations behind public investments. Additionally, it discusses the impact of such public investments on the local economy, assessing both the intended modernizing effects and the practical outcomes. This work contributes a detailed case study to the historical understanding of public investments in the Polish economy during the interwar period. It underlines the complex interplay between economic goals and actual managerial and technical outcomes, providing insights into the challenges and limitations of municipal-driven economic initiatives.